2002
DOI: 10.1063/1.1436533
|View full text |Cite
|
Sign up to set email alerts
|

Determining the locus for photocarrier recombination in dye-sensitized solar cells

Abstract: We present intensity-modulated photocurrent and infrared transmittance measurements on dye-sensitized solar cells based on a mesoporous titania (TiO2) matrix immersed in an iodine-based electrolyte. Under short-circuit conditions, we show that an elementary analysis accurately relates the two measurements. Under open-circuit conditions, infrared transmittance, and photovoltage measurements yield information on the characteristic depth at which electrons recombine with ions (the “locus of recombination”). For o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
75
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 14 publications
0
75
1
1
Order By: Relevance
“…From intensity-modulated infrared spectroscopy, Frank et al concluded that electron recombination near the FTO substrate is an important recombination route. 15) Recently, Yanagida group introduced that the thin Nb 2 O 5 layer works as a remarkable blocking layer at the FTO/TiO 2 interface, obtaining an increased cell performance. 13,16) Our group also investigated the positive effect of the underlayer on the cell performance of metal substrate based DSSC.…”
Section: )mentioning
confidence: 99%
“…From intensity-modulated infrared spectroscopy, Frank et al concluded that electron recombination near the FTO substrate is an important recombination route. 15) Recently, Yanagida group introduced that the thin Nb 2 O 5 layer works as a remarkable blocking layer at the FTO/TiO 2 interface, obtaining an increased cell performance. 13,16) Our group also investigated the positive effect of the underlayer on the cell performance of metal substrate based DSSC.…”
Section: )mentioning
confidence: 99%
“…PIA spectroscopy is frequently used in the field of conjugated polymers to investigate the nature and recombination kinetics of photogenerated species [5,6]. Recently, PIA measurements at a single wavelength in the near-infrared (frequency-resolved modulated www.elsevier.com/locate/cplett transmission) have been used to study dye-sensitized solar cells [7,8]. In this Letter we will present PIA spectra for both dye-sensitized solar cells and dye-sensitized TiO 2 films kept in air and determine the recombination rates under varying conditions from the frequency dependence of the PIA signals.…”
Section: Introductionmentioning
confidence: 99%
“…Film morphology is a crucial parameter in DSSCs' performance mainly to the influence in electron recombination rate. As referred in literature this phenomenon usually happens in the contact between TiO 2 film and conductive substrate (Zhu, et al, 2002). Therefore, a condensed non-porous thin film of TiO 2 is formed between nanocrystalline thick film and TCO substrate and referred as "blocking layer".…”
Section: Nanocrystalline Semiconductormentioning
confidence: 99%